Proton vs. Photon Radiation Therapy for Primary Gliomas: An Analysis of the National Cancer Data Base - Jhaveri, Jaymin; Cheng, En; Tian, Sibo; Buchwald, Zachary; Chowdhary, Mudit; Liu, Yuan; Gillespie, Theresa W.; Olson, Jeffrey J.; Diaz, Aidnag Z.; Voloschin, Alfredo; Eaton, Bree R.; Crocker, Ian R.; et al. (Frontiers in Oncology, 2018)
BACKGROUND: To investigate the impact of proton radiotherapy (PBT) on overall survival (OS) and evaluate PBT usage trends for patients with gliomas in the National Cancer Data Base (NCDB). METHODS: Patients with a diagnosis of World Health Organization (WHO) Grade I-IV glioma treated with definitive radiation therapy (RT) between the years of 2004-13 were identified. Patients were stratified based on WHO Grade and photon radiotherapy (XRT) versus PBT. Univariate (UVA) and multivariable analysis (MVA) with OS were performed by Cox proportional hazards model and log-rank tests. Propensity score (PS) weighting was utilized to account for differences in patient characteristics and to minimize selection bias. RESULTS: There were a total of 49,405 patients treated with XRT and 170 patients treated with PBT. Median follow-up time was 62.1 months. On MVA, the following factors were associated with receipt of PBT (all p < 0.05): WHO Grade I-II gliomas, treatment at an academic/research program, west geographic facility location, and surgical resection. After PS weighting, all patients treated with PBT were found to have superior median and 5-year survival than patients treated with XRT: 45.9 vs. 29.7 months (p = 0.009) and 46.1% vs. 35.5% (p = 0.0160), respectively. CONCLUSIONS: PBT is associated with improved OS compared to XRT for patients with gliomas. This finding warrants verification in the randomized trial setting in order to account for potential patient imbalances not adequately captured by the NCDB, such as tumor molecular characteristics and patient performance status.